Comparison of positive and negative cloud-to-ground lightning dominant storms in three regions of the United States - Anderson, Amanda R. S., author; Rutledge, Steven, advisor; Lang, Timothy, committee member; van den Heever, Sue, committee member; Robinson, R. Steven, committee member (Colorado State University. Libraries, 2011)
A statistical framework for analyzing storm data, called CLEAR (Colorado State University Lightning, Environment, Aerosols, and Radar), was used to examine the characteristics of seven storms in three different regions of the contiguous United States. Regions included the High Plains (eastern Colorado/western Kansas), central Oklahoma, and northern Alabama. Dual-polarization radar, lightning mapping array observations, and environmental reanalysis data were ingested by CLEAR to objectively assign lightning and environmental information to tracked storms. Comparison of environmental characteristics of the positive cloud-to-ground lightning (+CG) and negative cloud-to-ground lightning (-CG) dominant storms in the three regions showed no clear environmental difference between storms of different CG polarity dominance or between the regions themselves. Analysis of the lightning data showed the layer of maximum Very High Frequency (VHF) source density, inferred to be the positive charge layer, of the +CG dominant storms was at a much lower height (warmer temperature) than that of the -CG dominant storms. This indicated the probable existence of an inverted charge structure in the +CG dominant storms and supports previous research that suggested inverted charge as a cause of +CG dominance. Additionally, dual-Doppler analysis of the storms found that the +CG dominant storms had a much larger volume of >10 m s-1 updraft than the -CG dominant storms, which may contribute to the production of the inverted charge structure. The +CG dominant storms also had larger graupel echo volumes, consistent with the larger updraft volumes.
Keywords: lightning; regional comparison; positive dominance